Financial Incentives and Student Achievement: Evidence from Randomized Trials * - Fryer, Roland G. (Quarterly Journal of Economics, 2011)
This article describes a series of school-based field experiments in over 200 urban schools across three cities designed to better understand the impact of financial incentives on student achievement. In Dallas, students were paid to read books. In New York, students were rewarded for performance on interim assessments. In Chicago, students were paid for classroom grades. I estimate that the impact of financial incentives on student achievement is statistically 0, in each city. Due to a lack of power, however, I cannot rule out the possibility of effect sizes that would have positive returns on investment. The only statistically significant effect is on English-speaking students in Dallas. The article concludes with a speculative discussion of what might account for intercity differences in estimated treatment effects. Copyright 2011, Oxford University Press.